Magnetic Field in some Selected Directions of the Galaxy: Sagittarius Spiral Arm - Andreasyan, R. R.; Paronyan, G. M.; Sukiasyan, A. G.
Faraday rotation data on 180 pulsars are used in a detail study of the magnetic field in the direction of galactic longitude 40◦ < l < 70◦, including the Sagittarius spiral arm region. The highly regular magnetic field in northern hemisphere of galaxy is directed to the Sun, when the magnetic field of southern hemisphere is directed from the Sun. We propose that the Sagittarius spiral arm lies mainly to the north of the Galactic plane, while the magnetic field with opposite direction below this plane is the field of the halo of the southern hemisphere of the Galaxy.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture